CODE-MIXING AND LANGUAGE ATTITUDES IN JAPANESE CLASSROOMS: EVIDENCE FROM SENIOR SECONDARY SCHOOLS IN MEDAN - Nelvita; Fauzan Azizi Ilyas; M. Fachri Hidayat; Arga Lubis (Lire Journal (Journal of Linguistics and Literature), 2026)
This study examines bilingualism and Indonesian–Japanese code-mixing among senior secondary school learners of Japanese in Medan, focusing on how these practices shape classroom learning under limited instructional exposure. This study aims to identify the frequency, types, and functions of code-mixing in classroom interaction, describe students’ language attitudes in terms of pride, loyalty, and norm awareness, and derive pedagogical implications for strengthening sustained Japanese output. A sociolinguistic mixed-methods design was employed, combining a 21-item questionnaire with participant observation and interviews. The sample consisted of 341 students from five schools. Quantitative data were analysed descriptively, while qualitative data were used to identify recurrent functional patterns of code-mixing across classroom activities. The findings argue that language pride toward Japanese was relatively high, particularly in polite greetings and in positive perceptions of the language’s future relevance. However, language loyalty in peer interaction remained low, and norm awareness was stronger in pragmatic politeness than in structural accuracy. Code-mixing primarily functioned as a practical resource for classroom management, meaning negotiation, and maintaining task flow. Therefore, we conclude that stronger Japanese output depends less on motivation alone than on instructional conditions that transform positive attitudes into stable speaking routines through structured communicative practice.